Analisis Peluang dan Ancaman Perdagangan Internasional Furnitur Jati Jepara : Studi Kasus Perdagangan Indonesia Dengan Amerkia Serikat - Putri Mega Septiyani; Daspar (GLOBAL SCIENTS PUBLISHER, 2025)
The United States is one of Indonesia's main trading partners in the export of furniture products, particularly teak furniture from Jepara. Although the export value of Jepara’s teak furniture has shown significant growth from 2021 to 2023, Indonesia's market share in the U.S. remains small and is under strong pressure from competitors such as China and Vietnam. While the market potential is substantial, Indonesia faces global challenges such as potential U.S. import tariffs and the absence of a free trade agreement between the two countries. On the other hand, product quality, global image, and digitalization support serve as Indonesia’s competitive advantages. This study aims to analyze the opportunities and threats in the international trade of Jepara teak furniture and to provide an overview of strategic policies needed by the government and industry players to maintain competitiveness and export sustainability. With the right strategies, this sector is expected to strengthen its contribution to the national economy and expand its reach in the global market.